Revision Total Hip Arthroplasty in Osteogenesis Imperfecta - Schoof, Lauren H.; Duenes, Matthew L.; Feng, James E.; Long, William J.; Schwarzkopf, Ran (The Journal of Hip Surgery, 2020)
Osteogenesis imperfecta (OI) is a rare group of connective tissue disorders commonly associated with bone fragility, deformity, and fractures, leading to instability and early osteoarthritis. Current advancements in the medical and surgical management of OI have extended the life span of these patients, resulting in an increased need for joint arthroplasty to help maintain quality of life. However, surgery among this patient population is technically challenging and comes with a high burden of revision. In this report, we present a case of revision total hip arthroplasty in a patient with OI and review important considerations to help ensure proper preoperative planning and correct precautions to minimize complications and decrease implant failure.
Keywords: osteogenesis imperfecta; revision hip arthroplasty; bone fragility; complex total hip arthroplasty